Modulasi Single-Phase Shift Untuk Konverter DAB Pada Simulasi Typhoon HIL - Yohan Fajar Sidik; F. Danang Wijaya; Roni Irnawan; Muhammad Ridwan; Kevin Gausultan; Sriyono (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2024)
Solid-state transformer (SST) could be a solution for a future distribution system, in which many renewable energy sources (RES) are integrated. The SST consists of a single-phase dual-active bridge (DAB) converter, which is scale-down the dc voltage level. The control objective of the DAB converter used in the SST is to control its output voltage. This control strategy consists of a proportional-integral (PI) controller and a single-phase shift (SPS) modulation. Numerous literatures have mentioned about the SPS modulation for the DAB converter. However, they do not provide procedures in implementing the SPS modulation in the real controller. This paper aims to develop the SPS modulation in the real controller of the STM32F446RE microcontroller. The proposed SPS modulation is based on a master-slave timer feature, which is available in the STM32 microcontroller. The development process and testing of the complete control strategy of the DAB converter were carried out in the hardware-in-the-loop (HIL) simulation using Typhoon HIL. This scheme speeds up the development of process and reduces the costs. The experiment in the HIL environment shows that proposed control strategy of the DAB converter consisting of the PI controller and the SPS modulation is successfully implemented in the real microcontroller of the STM32F446RE. The proposed control strategy of the DAB converter is capable of bidirectional power flow, which is useful for integrating distributed generators in the load side. Moreover, this control strategy can reject the disturbance caused by loads.